Mapping immunotherapy potential: spatial transcriptomics in the unraveling of tumor-immune microenvironments in head and neck squamous cell carcinoma - Choi, Seo-Won; Kim, Jeong Heon; Hong, Jisu; Kwon, Minsu (Frontiers in Immunology, 2025)
Head and neck squamous cell carcinoma (HNSCC) often exhibits poor response rates to immune checkpoint inhibitor (ICI) therapies, largely owing to the intricate composition and spatial organization of immune cells within the tumor-immune microenvironment (TIME). The diversity of immune cell populations, their spatial relationships, and dynamic interactions significantly influence the immunosuppressive nature of the TIME, thereby limiting the efficacy of immunotherapy. To address these challenges and enhance the therapeutic potential of ICIs in HNSCC, a comprehensive analysis of the TIME is essential. Spatial transcriptomics (ST), a cutting-edge technology, enables high-resolution mapping of gene expression within the spatial context of the tumor, providing critical insights into the functional roles and interactions of immune cells in the TIME. This review highlights the importance of ST in uncovering the complexities of the TIME in HNSCC and proposes strategies for leveraging these insights to develop more effective immunotherapeutic approaches. By integrating spatial and molecular information, this review aims to pave the way for personalized and precision-based treatments in HNSCC, ultimately improving patient outcomes.